Abundant new computational wave solutions of the GM-DP-CH equation via two modified recent computational schemes - Khater, Mostafa M. A.; İnç, Mustafa; Attia, Raghda A. M.; Lu, Dianchen; Almohsen, Bandar (Taylor & Francis Ltd, 2020)
This work employs two new modified computational schemes to find the exact travelling and solitary wave solutions of the general modified Degasperis-Procesi Camassa-Holm (DP CH) equation that is used to illustrate the dynamical behaviour of shallow water. These schemes are the modified exponential expansion and the modified Khater methods that are used to formulate the computational solutions in various formulas such as trigonometric, hyperbolic, exponential functions. The obtained solutions are explained and figured out their substantial contributions in three different types of sketches (three, two-dimensional, and contour plots).
Keywords: The general modified Degasperis-Procesi-Camassa-Holm (DP CH) equation; computational recent modified schemes; solitary solutions